TECHNOLOGY FOR THE SEPARATION OF ANTHRACENE FROM THE SECONDARY PRODUCTS OF HYDROCARBON PYROLYSIS - Nurmanov Suvonqul Erhonovich,; Ziyadullayev Anvar Egamberdiyevich,; Ziyadullayev Anvar Egamberdiyevich,; To'rayeva Dilrabo Fakhriddinovna, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Introduction Hydrocarbon  pyrolysis  is  a  process  of  thermal  decomposition  of  organic substances under high temperature conditions, resulting in the formation of valuable aromatic hydrocarbons. Among the secondary products released in this process are polycyclic  aromatic  hydrocarbons  such  as  anthracene,  phenanthrene,  naphthalene, which are widely used in organic synthesis, pharmaceuticals and the production of dyes. Anthracene  is  mainly  extracted  from  coal  tar,  but  it  is  also  found  in  certain quantities in oil and gas pyrolysis products. Improving the technology of anthracene extraction and its high purity extraction is one of the urgent problems of the industry. This  work  aims  to  develop  a  technology  for  extracting  anthracene  from  the  tarry fractions formed as a result of pyrolysis and to conduct its scientific and statistical analysis.